Resurrect Multicultural Islamic Education in Indonesia - Dwi Mariyono; Maskuri Maskuri (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Indonesia in multicultural education has not yet shown significant results within the framework of multicultural education, even though Islamic education in Islamic boarding schools has unconsciously implemented it first. This study aims to describe, analyze and interpret how to revive multicultural Islamic education in Indonesia. This type of research is qualitative with literature review method. The main objects in this research are books, journals, articles, and other scientific literature related to the research topic. Social theory and multicultural theories are also searched by researchers and collected as complementary data. After the data is collected, it is reviewed and analyzed using the interactive model theory of Huberman and Saldana (2014). From the results of the analysis it was found that: 1) Multicultural Islamic Education is a paradigm of the social life of the world community which is united in the celestial ontology (Al-Qur'an and Al-Hadith along with the principles of the imams); 2). The ideas and mission of Ibn Khaldun's education which are oriented towards the friendliness of the world's values and the values of the hereafter, deserve to be used as a reference and reference for the implementation of Multicultural Islamic Education; 3). Islam, with its slogan that originates from heaven, as rohmatan lil'almin, implies that there is no element of distinction between all earthly creatures with all their labels (religion, culture, customs, ethnicity, language, class) and other diversity. 4). The symbol of Bhinneka Tunggal Ika, which is in line with the concept of heaven, should not only be used as a motto, but must be instilled into the foundations of community education life. 5). Textbooks of Islamic Education that are friendly, tolerant, uphold mutual understanding and respect need to be printed and campaigned on a large scale. 6). There is a need to integrate various histories into historical subject units, because history is an original and liner fact. It is with history that we know the conditions of the beginning, the golden age, the destruction and the rise of the former nations with all their behavior, morals and ethics. The results of this study are expected to be used as information and references for other researchers with literature studies on Multicultural Islamic Education.